O9 Reduction of interferon-γ and elevated baseline cytotoxic gene expression in the blood associate with ustekinumab response in SLE. (23rd March 2020) - Seridi, Loqmane; Cesaroni, Matteo; Loza, Matt; Schreiter, Jessica; Sweet, Kristen; Campbell, Kim; Lipsky, Peter; Vollenhoven, Ronald van; Hahn, Bevra H; Tsokos, George C; Chevrier, Marc; Rose, Shawn; et al.
Abstract : Background/Purpose: Ustekinumab (anti-IL-12/23) improved SLE-disease activity vs. placebo in patients with active SLE despite standard therapy. 1 We investigated whether biomarkers collected in this trial could distinguish responders (UST-R) from non-responders (UST-NR) (response defined by SLE Responder Index-4 at week 24) and if these features could help elucidate the mechanism of action of ustekinumab in SLE. Methods: We examined whole blood RNA and serum at baseline and longitudinally from this trial of 102 seropositive SLE patients, plus age- and sex-matched healthy controls. Targeted proteomic analysis used ELISA, and gene expression analysis used microarray. RNA-Seq was performed on whole blood stimulated in vitro. Results: Changes in serum IL-17A, IL-17F and IL-22 were subtle and did not consistently associate with UST response, while no modulation of type I interferon levels was observed. In contrast, durable reduction in IFN-γ protein occurred only in UST-R. These biomarker effects were sustained through Week 48. A non-biased machine-learning algorithm identified a novel 9-gene (PRF1, KLRD1, GZMH, NKG7, GNLY, FGFBP2, TRGC2, TARP, TRGV2) cytotoxic gene-signature (CGS) enriched in baseline blood samples of UST-R vs UST-NR, which was corroborated using a published NK-cell CGS (figure 1 ). No significant differences in these gene-signatures were observed between placebo responders vs non-responders. In contrast, decreased expression levels were observed over the course of 24 weeks for both signatures only in the UST-R population. After whole-blood stimulation with recombinant IL-12, but not IL-23, expression of representative members of the CGS increased. Conclusion: We identified a novel cytotoxic signature in baseline blood samples that associated with UST response in SLE. Targeted biomarker analysis suggests an important role of IL-12 blockade in the mechanism of action of UST in SLE. Acknowledgement: This work was supported by Janssen Research & Development, LLC. Reference: Van Vollenhoven R.F., Hahn, B.H., Tsokos, G.C., et al. Efficacy and safety of ustekinumab, an IL-12 and IL-23 inhibitor, in patients with active systemic lupus erythematosus: results of a multicentre, double-blind, phase 2, randomised, controlled study. Lancet . 2018;392:1330–1339.